Key insights and new approaches that are advancing the understanding of Internet Addiction Disorder and Depression in adolescen - Wallace, Brian E.; Masiak, Jolanta; Pabis, Matthew R. (Polish Journal of Public Health, 2013)
The Internet is a popular and useful tool that has become an integral part of the lifestyle in many cultures but it can also be the focus and cause of psychosocial problems leading to Pathological Internet Use (PIU) or Internet Addiction Disorder (IAD). IAD is a growing international concern which involves a small but significant number of the Internet users who gradually lose control of the time allotted to their online activity and continue “surfing” the Internet despite its damaging effects regarding their social and psychological welfare. Overuse of the Internet often has negative impacts with regard to an affected individual’s occupation or academic performance as well as their relationships and finances.IAD commonly incorporates a myriad of symptoms, which may include craving, preoccupation, loss of control, psychomotor agitation, anxiety, hostility, withdrawal, and depression. Although the associations of IAD with social, educational, and physical variables have often been investigated since the disorder was first recognized in the late 1990s, less attention has been paid to documenting its correlations with mental variables such as depression, anxiety, and stress. However, an increasing proportion of psychological research is beginning to focus on the relationship between problematic Internet usage and depression.This review article examines the current scientific literature discussing the associations between IAD and depression in adolescents and university students. Specifically, this article will examine several studies dealing with depression as a symptom, comorbidity, an essential component of an emerging cycle that may enhance symptoms of IAD, and as a multidimensional symptom measure in IAD. The article will also discuss new research approaches for dealing with the adolescent and university student populations, the importance of recognizing and treating underlying depression in IAD, and the need to increase regional IAD research, especially in central and eastern Europe